2013
DOI: 10.1159/000353097
|View full text |Cite
|
Sign up to set email alerts
|

Renal Dysfunction and Atherosclerosis of the Neointima following Bare Metal Stent Implantation

Abstract: Background: Recently, neoatherosclerosis within the neointima after bare metal stent (BMS) implantation, which could cause late restenosis and very late stent thrombosis, has been a cause of concern. Renal dysfunction has been related to late cardiovascular events after coronary intervention. The present study was conducted focusing on the relationship between renal dysfunction and neointimal tissue characteristics with BMS restenosis using integrated backscatter intravascular ultrasound (IB-IVUS). Methods: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…It was found to be a factor independently associated with ISR presenting as MI [11]. This is likely explained by the increased incidence of neoatherosclerosis and higher lipid content in neointima among patients with CKD [28, 37].…”
Section: Discussionmentioning
confidence: 99%
“…It was found to be a factor independently associated with ISR presenting as MI [11]. This is likely explained by the increased incidence of neoatherosclerosis and higher lipid content in neointima among patients with CKD [28, 37].…”
Section: Discussionmentioning
confidence: 99%
“…CRF is a predictor of neoatherosclerosis 19 and increased lipid neointimal content after stenting. 21 These characteristics may explain the CRF association with ACS presentation in the BMS era, 2,4 and the late catch-up phenomenon after DES implantation, mainly manifesting as ACS. 22 Together, these findings suggest that the ISR clinical presentation is associated with patient-and not device-related factors.…”
Section: Correlates Of MI As Isr Presentationmentioning
confidence: 99%
“…Baber et al ( 22 ) characterized coronary atherosclerotic plaque morphology in CKD patients using intravascular ultrasound and demonstrated that CKD patients have plaque composed of greater necrotic core and less fibrous tissue prone to rupture. Similarly, Hayano et al ( 27 ) demonstrated that impaired renal function was related to higher percentage of lipid volume within the neointima after stent implantation leading to an increased risk of late stent failure. In addition, it has been reported that impaired renal function causes decreased number of smooth muscle cells within the plaque that may cause loss of fibrous cap of plaque ( 28 ).…”
Section: Discussionmentioning
confidence: 93%